Regret-based capital asset pricing model - Qin, Jie (Journal of Banking & Finance, 2020)
This study examines the influence of regret aversion on asset pricing by proposing a regret-based capital asset pricing model in which individuals maximize the expected returns from chosen portfolios of assets while minimizing anticipated regrets. In equilibrium, a closed-form pricing formula is derived, whereby a risky asset's excess return is proportional to its “regret beta” that measures the exposure to investors’ emotions. The market as a whole pays investors a positive “regret premium” as compensation for regret aversion. As such, this study proposes a conceptual framework to understand the aggregate effects of regret. The model indicates that employing a regret-related beta can help explain cross-sectional returns. It also implies that regret aversion is a possible reason for the flat security market line and high equity premium.